Evidence for a bimodal distribution of Escherichia coli doubling times below a threshold initial cell concentration - Chen Chin-Yi; Paoli George C; Nguyen Ly-Huong T; Irwin Peter L (BMC Microbiology, 2010)
Abstract Background In the process of developing a microplate-based growth assay, we discovered that our test organism, a native E. coli isolate, displayed very uniform doubling times (τ) only up to a certain threshold cell density. Below this cell concentration (≤ 100 -1,000 CFU mL-1 ; ≤ 27-270 CFU well-1) we observed an obvious increase in the τ scatter. Results Working with a food-borne E. coli isolate we found that τ values derived from two different microtiter platereader-based techniques (i.e., optical density with growth time {=OD[t]} fit to the sigmoidal Boltzmann equation or time to calculated 1/2-maximal OD {=tm} as a function of initial cell density {=tm[CI]}) were in excellent agreement with the same parameter acquired from total aerobic plate counting. Thus, using either Luria-Bertani (LB) or defined (MM) media at 37°C, τ ranged between 17-18 (LB) or 51-54 (MM) min. Making use of such OD[t] data we collected many observations of τ as a function of manifold initial or starting cell concentrations (CI). We noticed that τ appeared to be distributed in two populations (bimodal) at low CI. When CI ≤100 CFU mL-1 (stationary phase cells in LB), we found that about 48% of the observed τ values were normally distributed around a mean (μτ1) of 18 ± 0.68 min (± στ1) and 52% with μτ2 = 20 ± 2.5 min (n = 479). However, at higher starting cell densities (CI>100 CFU mL-1), the τ values were distributed unimodally (μτ = 18 ± 0.71 min; n = 174). Inclusion of a small amount of ethyl acetate to the LB caused a collapse of the bimodal to a unimodal form. Comparable bimodal τ distribution results were also observed using E. coli cells diluted from mid-log phase cultures. Similar results were also obtained when using either an E. coli O157:H7 or a Citrobacter strain. When sterile-filtered LB supernatants, which formerly contained relatively low concentrations of bacteria(1,000-10,000 CFU mL-1), were employed as a diluent, there was an evident shift of the two populations towards each other but the bimodal effect was still apparent using either stationary or log phase cells. Conclusion These data argue that there is a dependence of growth rate on starting cell density.